Case Report: Treatment of Anti-MDA5-Positive Amyopathic Dermatomyositis Accompanied by a Rapidly Progressive Interstitial Lung Diseases With Methylprednisolone Pulse Therapy Combined With Cyclosporine A and Hydroxychloroquine - Zhang, Qia-Chun; Liu, Min-Ying; Chen, Zhi-Xin; Chen, Yimin Talia; Lin, Chang-Song; Xu, Qiang (Frontiers in Medicine, 2020)
Introduction: Patients with anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive amyopathic dermatomyositis (ADM) often develop rapidly progressive interstitial lung diseases (RP-ILD), with poor treatment success. Many studies have shown that this is the main cause of death in patients with anti-MDA5 antibody-positive ADM. Case Presentation: A 37-years-old woman developed a cough, shortness of breath, and a rash on both hands, which resembled Gottron's signs. Upon laboratory examination, the results were as follows: antinuclear antibody (ANA) positive; anti-Ro52 antibody positive; and anti-MDA5 antibody positive. Pulmonary high-resolution CT (HRCT) scan showed pulmonary interstitial inflammatory changes, and mediastinal and subcutaneous emphysema. She was finally diagnosed with anti-MDA5 antibody-positive ADM accompanied by RP-ILD. She was first given high-dose-steroid pulse therapy with methylprednisolone (500 mg per day for 3 days) followed by methylprednisolone (40 mg, daily), cyclosporine A (100 mg, twice per day), and hydroxychloroquine (200 mg, twice per day). Since her discharge from our hospital in March of 2018, she has maintained the methylprednisolone therapy (tapered to 10 mg daily), cyclosporine A (100 mg, twice per day), and hydroxychloroquine (200 mg, twice per day). Outcomes: Pulmonary HRCT scans taken on 4, 9, and 26 months after her discharge from our hospital showed that the interstitial pneumonitis had significantly improved and that mediastinal and subcutaneous emphysema had been gradually absorbed. The patient can now participate in regular work and activities of daily living. Conclusion: The treatment of methylprednisolone pulse therapy combined with cyclosporine A and hydroxychloroquine may be an option for the RP-ILD accompanied by anti-MDA-positive ADM. After the acute phase, this combination therapy strategy is helpful to the disease control of patients.